Optimizing nitrogen management practices to enhance nutrient use efficiency and growth of maize (Zea mays L.) - Budha, Janaki; Bhatta, Sandesh; Ram Khanal, Babu; Thapa, Vesh Raj (Food Agricultural Sciences and Technology, 2026)
Efficient nitrogen (N) management is crucial for improving growth, yield, and nitrogen use efficiency (NUE) of maize (Zea mays L.) while maintaining environmental quality. This study evaluated growth parameters, yield attributes, soil nutrient dynamics, nitrogen uptake, and NUE under various N sources and management practices on the sandy loam soil of Chitwan, Nepal. The experiment was designed as a randomized complete block with three replications, incorporating the following treatments: N check, N all at basal dose, N at three split doses, polymer-coated urea (PCU), neem-coated urea (NCU), urea deep placement (UDP), leaf color chart (LCC ≤4.5), and soil plant analysis development (SPAD ≤40) meter. The results depicted that the slow-releasing nitrogen sources, such as PCU, NCU, and UDP, along with split applications, outperformed conventional methods significantly. PCU emerged as the most effective treatment, achieving the highest plant height, yield, and nitrogen uptake. Compared to conventional applications, PCU increased grain yield by 11.2%, LCC (≤4.5) improved agronomic efficiency by 54.2%, and UDP enhanced recovery efficiency by 61.5%. These findings suggest that integrating slow-release and split-application practices can optimize N use and support sustainable maize production, with PCU being the best among all other treatments.